Managerial accounting : information for decisions - Ingram, Robert W.; Albright, Thomas L.; Hill, John W. (Cincinnati, OH : South-Western College, 2001)
This book is divided into three parts: Products costing and decision making; Control, Measurement, and evaluation; and Expanded topics.
Keywords: Accounting; Managerial accounting